Rios nossos que estão no sertão! São Francisco e Parnaíba - Gercinair Silvério Gandara (Confins)
The northeast region of Brazil has a modest hydrography. The majority of the rivers in this region are classified as temporary except the Maranhão rivers, which are mostly perennial. They cover a vast territorial extension and form almost always each a basin. The set of these basins is usually called Northeast Basin. In the states of Piauí and Bahia the natural and geographical conditions of the Parnaíba and São Francisco river had special significance in the composition of space and hence in the formation of its history. The environmental assets of both valleys and rivers abound. In both basins the fundamental problems were territorial occupation in modern civilization bases. The course of the rivers became aggregators of people and “avenues” of interior settlement. Liquid paths! Historically the traces of both rivers would mean nothing, but from the environmental and human content of the water spout stories, which is why we chose to confront, through a comparative analysis, these two river basins. The debate that stems from these rivers are (r) productions of reality read in their own landscapes so they could not be thought without taking into account their geographical landscape, nature and also their waters, therefore weather and time. This comparison was / is / will be perfectly possible!